2020
DOI: 10.1016/j.scitotenv.2019.134055
|View full text |Cite
|
Sign up to set email alerts
|

Growth, wood anatomy and stable isotopes show species-specific couplings in three Mexican conifers inhabiting drought-prone areas

Abstract: An improved understanding of how tree species will respond to warmer conditions and longer droughts requires comparing their responses across different environmental settings and considering a multi-proxy approach. We used several traits (tree-ring width, formation of intra-annual density fluctuations -IADFs, wood anatomy, ∆ 13 C and δ 18 O records) to retrospectively quantify these responses in three conifers inhabiting drought-prone areas in northwestern Mexico. A fir species (Abies durangensis) was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 59 publications
0
9
0
2
Order By: Relevance
“…A growing body of evidence shows that plants can close their stomata during drought events to avoid unnecessary water loss. Consequently, stomatal conductance to CO 2 decreases and Rubisco fixes a higher-than-usual proportion of 13 C compared to 12 C. As a result, rings are formed in which the cellulose is enriched in the heavier isotope, which translates as less negative isotopic signatures and those large anomalies in their δ 13 C can be indicators of forest health [106][107][108][109]. Other studies of co-occurring healthy and dead trees found a lower i WUE in dead trees, suggesting either a reduction in photosynthesis rates or, more probably, a poor regulation of stomatal conductance [110][111][112].…”
Section: Tree Response To Droughtmentioning
confidence: 99%
“…A growing body of evidence shows that plants can close their stomata during drought events to avoid unnecessary water loss. Consequently, stomatal conductance to CO 2 decreases and Rubisco fixes a higher-than-usual proportion of 13 C compared to 12 C. As a result, rings are formed in which the cellulose is enriched in the heavier isotope, which translates as less negative isotopic signatures and those large anomalies in their δ 13 C can be indicators of forest health [106][107][108][109]. Other studies of co-occurring healthy and dead trees found a lower i WUE in dead trees, suggesting either a reduction in photosynthesis rates or, more probably, a poor regulation of stomatal conductance [110][111][112].…”
Section: Tree Response To Droughtmentioning
confidence: 99%
“…However, the WUE i should not be considered as equivalent to instantaneous WUE, which is the ratio of assimilation (carbon gained) to transpiration (water lost) and takes into account the atmospheric water demand (Pacheco et al, 2020; Seibt et al, 2008). Thus, the equation used is the “simple” form of isotopic discrimination that does not include effects due to mesophyll conductance and photorespiration, which were not available for the study species.…”
Section: Methodsmentioning
confidence: 99%
“…These results can be attributed to the pine wood anatomy and its low specific gravity associated with the presence of long and wide tracheids prone to be filled with resin, which transversely communicate to each other by radial pits (Acosta et al, 2020c). For Pacheco et al (2020), the lumens of tracheids belonging to a pine wood are of variable diameter with an average of ≈30 μm. The incorporated resin remained well retained since both woods presented mean leaching index below 2% (Fig.…”
Section: Treatment Parametersmentioning
confidence: 99%